Proof of life Castle Rock Entertainment presents in association with Bel-Air Entertainment an Anvil Films Production ; produced by Taylor Hackford and Charles Mulvehill ; written by Tony Gilroy ; directed by Taylor Hackford. - Hackford, Taylor, 1944-; Gilroy, Tony; Mulvehill, Charles; Ryan, Meg; Crowe, Russell, 1964-; Reed, Pamela; Caruso, David, 1956-; Morse, David; Bel-Air Entertainment (Firm); Castle Rock Entertainment (Firm); Warner Bros. Pictures (1969- ); Anvil Films (United States) (UK : Warner Home Video, 2008)
Rebels in a politically volitile Latin American country have kidnapped Alice Bowman's husband for ransom, $3 million. Terry Thorne is the hostage retrieval expert who becomes Alice's only hope in navigating a high-stacks game where terrorists value money over life.
Special features: Feature-length audio commentary by director Taylor Hackford -- Behind-the-scenes documentary The making of Proof of life -- Interactive Menus -- Scene Access -- Trailer.
Originally released as a motion picture in 2000.
Special features: Feature-length audio commentary by director Taylor Hackford -- Behind-the-scenes documentary The making of Proof of life -- Interactive Menus -- Scene Access -- Trailer.
Meg Ryan, Russell Crowe, David Morse, Pamela Reed and David Caruso.
DVD, widescreen presentation; Dolby Digital.
Includes English with optional English, French, Romanian and Bulgarian subtitles; optional English subtitles for hearing impaired.
Keywords: Kidnapping -- Drama; Feature films; Fiction films